IMPROVING THE QUALITY OF VIBRATION DIAGNOSTICS OF AGRICULTURAL EQUIPMENT UNITS - VOYTSYTSKY, ANATOLY; NEZDVETSKA, INNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
It is known that friction and vibrations are the main factors affecting the condition of the equipment during its operation. Therefore, monitoring and diagnostics of vibration resistance of machines and mechanisms are of great importance for their effective operation. This article will present and describe methods of vibroacoustic diagnostics, which are simple and sensitive for detecting defects in various mechanisms and machines, in particular in the agricultural sector. One of the key elements used to diagnose and control the degree of wear of parts is a piezoelectric transducer. It is easy to use and highly accurate. Such converters are almost not affected by electric and magnetic fields, acoustic signals and other mechanical vibrations, except in certain cases. This article will consider the improvement of the piezoelectric transducer, which can be used to measure the vibration rate of oscillations of elements and assemblies of agricultural machines. The technical solution includes the use of a differential amplifier with buffer stages connected to a basic differential amplifier. This approach allows you to reduce the impact of out-of-band interference and increase measurement accuracy. The use of a common-mode perturbation voltage is also an important element in the improved piezoelectric transducer, helping to provide more accurate results. This article reveals important aspects of vibration diagnostics and offers a new technical solution to improve measurements. It will be useful for specialists in the field of mechanical engineering and agricultural industry, who are interested in effective control and support of machines and mechanisms during their work.